Mass spectrometry based molecular profile dissects the complexity of traditional Chinese medicine. Issue 7 (16th March 2015) - Liu, Wenhu; Guo, Xiaojuan; Li, Qiang; Xu, Guang; Feng, Mengpei; Guan, Tianbing; Yan, Leyu; Nie, Wenna; Parker, Tony; Lv, Haitao
Abstract : Mass spectrometry driven molecular profiles for systematically dissecting the chemical complexity of traditional Chinese medicine. Abstract : Traditional Chinese Medicine (TCM) has yielded various medical benefits for the prevention and treatment of numerous diseases in China, Asian countries and Western countries. Yet, TCM acts as an important complement to modern Western medicine for facilitating drug discovery and development. However, many questions have emerged with TCM development, highlighting the chemical complexity, the fact that TCM preparations contain undefined bioactive compounds that lead to unidentified mechanisms of action, toxicity and adverse effects. These questions concerning the therapeutic efficacy, molecular mechanisms of action and safety issues have prevented broader applications of TCM in the biomedical niche related to drug discovery and development. This review explores the applicability of metabolomics as a systems biology strategy for addressing the above questions associated with the TCM field, which is supposed to considerably promote modern drug discovery and development.